2019
DOI: 10.35631/aijbes.11001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation and Organizational Performance of E-Business in Malaysia: The Moderating Role of External Environment

Abstract: There has been relatively little research that examines the relationship between the external environment and their consequences on the organizational performance of e-business in developing countries. This research represents an attempt to do so from the Malaysian e-business perspectives. This research examines the relationships between entrepreneurial orientation and organizational performance and on the role of the external environment as a moderator between the relationships. The consideration of putting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Meanwhile, KMP is significantly related with the other two variables of EO; risk-taking and proactiveness, and thus, it supports H3c and H3d . This result is aligned with studies by Adam et al (2018a, 2018b) and Madhoushi et al (2011) that found that KMP significantly mediated the relationship between EO and EA. These significant results supported the statement that KMP can be used as a leverage point that makes EO able to influence the decision on EA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, KMP is significantly related with the other two variables of EO; risk-taking and proactiveness, and thus, it supports H3c and H3d . This result is aligned with studies by Adam et al (2018a, 2018b) and Madhoushi et al (2011) that found that KMP significantly mediated the relationship between EO and EA. These significant results supported the statement that KMP can be used as a leverage point that makes EO able to influence the decision on EA.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is aligned with the studies by Latif et al (2020), Gupta and Moesel (2007); and Stuetzer et al (2018) that found a relationship of EO on KM processes, although one or two of EO’s dimensions are not specifically mentioned. The EO also relates to knowledge utilization (Wach et al , 2018; Adam et al , 2018a, 2018b), knowledge sharing (Hormiga et al , 2017) and knowledge creation (Jiang et al , 2019), although its relationship is limited. This can be associated with why innovativeness has an insignificant relationship toward KMP, which does not support H2d .…”
Section: Discussionmentioning
confidence: 99%
“…For five decades, organisational performance has been widely researched by academic scholars and business practitioners (Adam et al ., 2018). Organisational performance has been analysed in terms of normative and descriptive explanations in strategic planning research for continuous improvement in managing organisational performance (Buddika et al ., 2016).…”
Section: Strategic Managementmentioning
confidence: 99%
“…Academic scholars and practitioners have highlighted the importance of strategic management in measuring organisational performance in terms of innovation, entrepreneurship, technology, knowledge, economics, healthcare and organisational performance (Adam et al, 2018(Adam et al, , 2020Alosani et al, 2020). Conversely, there is a knowledge gap on the effective judgement practices of strategic management enablers and organisational performance during decision-making (Abuhjeeleh et al, 2018;Acciarini et al, 2021;Elrehail et al, 2020;Nguyen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kaplan and Norton (2005) emphasise that organisational performance is the prerequisite of performance improvement. In these studies, Balanced Scorecard was utilized in quantifying the public sector performance as it facilitated financial and non-financial aspects of organisational performance and covered all four measurement perspectives consisted of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective of non-profit organisations (Adam et al, 2018;Tsai et al, 2020). Performance measurement is a systematic series of mechanism to identify the effectiveness and efficiency of peoples' behaviours, and it is also known as a setting in order for the people to perform their utmost abilities.…”
Section: Organisational Performance (Op)mentioning
confidence: 99%